2014
DOI: 10.1097/qai.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Virologic and Immunologic Outcomes of HIV-Infected Ugandan Children Randomized to Lopinavir/Ritonavir or Nonnucleoside Reverse Transcriptase Inhibitor Therapy

Abstract: Background In the PROMOTE-pediatrics trial, HIV-infected Ugandan children randomized to receive lopinavir-ritonavir (LPV/r)-based antiretroviral therapy (ART) experienced a lower incidence of malaria compared to children receiving non-nucleoside-reverse-transcriptase-inhibitor (NNRTI)-based-ART. Here we present the results of the non-inferiority (NI) analysis of virologic efficacy and comparison of immunologic outcomes. Methods ART-naïve or -experienced (HIV RNA < 400 copies/ml) children ages 2 months to 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…An underpowered subanalysis by individual drug in children younger than 3 years of age found no difference in virological outcome between children on NVP‐ and LPV/r‐containing ART regimens (G. Tudor‐Williams, unpublished results). In agreement with PENPACT‐1, the Prevention of Malaria and HIV Disease in Tororo, Uganda (PROMOTE) study, a small open‐label RCT in Uganda of children aged 0.4–5.9 (median 3.1) years not exposed to NVP, showed comparable results at 48 weeks in terms of virological suppression, CD4 gain and severe adverse events for NNRTI‐ and LPV/r‐containing ART regimens 71.…”
Section: Which Art Regimen To Start As First‐line Therapysupporting
confidence: 65%
See 4 more Smart Citations
“…An underpowered subanalysis by individual drug in children younger than 3 years of age found no difference in virological outcome between children on NVP‐ and LPV/r‐containing ART regimens (G. Tudor‐Williams, unpublished results). In agreement with PENPACT‐1, the Prevention of Malaria and HIV Disease in Tororo, Uganda (PROMOTE) study, a small open‐label RCT in Uganda of children aged 0.4–5.9 (median 3.1) years not exposed to NVP, showed comparable results at 48 weeks in terms of virological suppression, CD4 gain and severe adverse events for NNRTI‐ and LPV/r‐containing ART regimens 71.…”
Section: Which Art Regimen To Start As First‐line Therapysupporting
confidence: 65%
“…The results of the ARROW trial in children have also shown clinical monitoring to be a safe and effective alternative to laboratory monitoring, in resource‐poor settings 71. This supports a recommendation that monitoring of CD4 count and laboratory tests for drug toxicity can safely be performed less frequently than every 3 months when a child is clinically well, has had VL < 50 copies/ml for over 1 year and is not severely immunosuppressed.…”
Section: Monitoring On Artmentioning
confidence: 55%
See 3 more Smart Citations